2020
DOI: 10.3390/cells9051272
|View full text |Cite
|
Sign up to set email alerts
|

Secretome of Mesenchymal Stromal Cells Prevents Myofibroblasts Differentiation by Transferring Fibrosis-Associated microRNAs within Extracellular Vesicles

Abstract: Fibroblasts differentiation into myofibroblasts is a central event of tissue fibrosis. Multipotent mesenchymal stromal cells (MSCs) secretome can interfere with fibrosis development; despite precise underlying mechanisms remain unclear. In this study, we tested the hypothesis that MSC secretome can affect fibroblast’ differentiation into myofibroblasts by delivering regulatory RNAs, including microRNAs to these cells. Using the model of transforming growth factor-beta (TGFbeta)-induced fibroblast differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 49 publications
5
52
0
1
Order By: Relevance
“…Noteworthy, any fibroblast could fit in MSC definition, however, the relationship between phenotype and cell function may be ambiguous. Thus, we and others have demonstrated in some studies the substantial differences in regenerative effects of so-called MSCs and so-called fibroblasts (Gatti et al, 2011;Basalova et al, 2020).…”
Section: Current Understanding Of Mscsmentioning
confidence: 86%
See 2 more Smart Citations
“…Noteworthy, any fibroblast could fit in MSC definition, however, the relationship between phenotype and cell function may be ambiguous. Thus, we and others have demonstrated in some studies the substantial differences in regenerative effects of so-called MSCs and so-called fibroblasts (Gatti et al, 2011;Basalova et al, 2020).…”
Section: Current Understanding Of Mscsmentioning
confidence: 86%
“…In addition to the secretion of individual paracrine factors, MSCs can secrete EV, mostly exosomes (Basalova et al, 2020 ), whose composition also varies depending on external signals (Lopatina et al, 2014 ). The significance of this cell communication mechanism is crucial because MSCs can transmit molecules of various nature, including proteins, lipids, and nucleic acids such as mRNA and regulatory non-coding RNAs, within EV to target cells (Kalinina et al, 2015b ; Yáñez-Mó et al, 2015 ; Efimenko et al, 2016 ; Basalova et al, 2020 ). Due to the possible targeted effects of EV, their transfer to nearby cells can help fine-tune the effects of the MSC secretome (Hoshino et al, 2015 ).…”
Section: Mechanisms Of Msc Participation In Tissue Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased MMP-9 and CH13L1 levels in exosomes, and extracellular matrix modulating and fibrosis-promoting exosomal activity may play especially important roles in TED, as orbital tissue remodeling and fibrosis are integral parts of the disease mechanism. Previous reports showed that nuclear Sp1 protein is more abundant in orbital fibroblasts, and its binding to specific sites on DNA is greater than regular fibroblasts to modulate cytokine response [ 43 , 44 ]. Moreover, SP1 was shown to be the main target of delivered miRs in leukemic [ 45 ] and other cancer models [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like their parent cells, exosomes have been reported to stimulate cellular regeneration, functional recovery in various pathological conditions ( Derkus et al, 2017 ). Moreover, recently MSC-derived EVs have been reported to suppress fibrosis by preventing differentiation of fibroblasts into myofibroblasts ( Basalova et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%